Mediatization of East Asia in James Bond films. (June 2018) - Pua, Phoebe; Hiramoto, Mie
Highlights: East Asian identity constructed via stereotyped and mediatized linguistic performance. Standard Accents enable major villains to appear menacing, ensures dialogue clarity. All other villains reveal distinct, if not complete, lack of English proficiency. Allies speak with L2 accents, incorporate racial indexes to speech and performance. Abstract: In the last 50 years, the name James Bond has become synonymous with masculine sophistication. Through iconic characteristics of confidence and wit, Bond's image as a debonair Englishman has been carefully orchestrated and upheld. For this, much credit is due to the many secondary characters who exist primarily to index him as the ideal man, often at their expense. To achieve this, the films frequently employ methods of othering, particularly through exaggerating racial identities to the point of exoticization. While accusations that the Bond film series is riddled with racial stereotypes are not new, there exist gaps in scholarship addressing East Asian presence and stereotypes. This paper investigates (mis)representations of East Asian characters, examining them separately as allies and villains, through analyzing processes which mediatize their languages and cultures. Ultimately, it confronts the mediatization processes of East Asia within the Bond film series and explores the social meanings enregistered therein.